CAPACITY BUILDING OF STATE ELEMENTARY SCHOOL 206 TEACHER GROUPS IN IMPLEMENTING THE BANDUNG MASAGI PILAR LOVE FOR THE ENVIRONMENT PROGRAM IN THE CITY OF BANDUNG - Imas Sumiati; Hari Busthomi Ariffin; Yayan Mulyana (LPM Universitas Pasundan, 2021)
The existence of partners who will be selected by the implementing team are teachers who teach at STATE ELEMENTARY SCHOOL (SDN) 206 Putraco Indah Bandung. Partners were chosen because they have not fully implemented the Bandung city government program, namely